An overview on the identification of MAIT cell antigens. Issue 6 (15th May 2018) - Kjer‐Nielsen, Lars; Corbett, Alexandra J; Chen, Zhenjun; Liu, Ligong; Mak, Jeffrey YW; Godfrey, Dale I; Rossjohn, Jamie; Fairlie, David P; McCluskey, James; Eckle, Sidonia BG
Abstract: Mucosal associated invariant T (MAIT) cells are restricted by the monomorphic MHC class I‐like molecule, MHC‐related protein‐1 (MR1). Until 2012, the origin of the MAIT cell antigens (Ags) was unknown, although it was established that MAIT cells could be activated by a broad range of bacteria and yeasts, possibly suggesting a conserved Ag. Using a combination of protein chemistry, mass spectrometry, cellular biology, structural biology and small molecule chemistry, we discovered MR1 ligands derived from folic acid (vitamin B9) and from an intermediate in the microbial biosynthesis of riboflavin (vitamin B2). While the folate derivative 6‐formylpterin generally inhibited MAIT cell activation, two riboflavin pathway derivatives, 5‐(2‐oxopropylideneamino)‐6‐D‐ribitylaminouracil and 5‐(2‐oxoethylideneamino)‐6‐D‐ribitylaminouracil, were potent MAIT cell agonists. Other intermediates and derivatives of riboflavin synthesis displayed weak or no MAIT cell activation. Collectively, these studies revealed that in addition to peptide and lipid‐based Ags, small molecule natural product metabolites are also ligands that can activate T cells expressing αβ T‐cell receptors, and here we recount this discovery. Abstract : Mucosal associated invariant T (MAIT) cells are restricted by the monomorphic MHC class I‐like molecule, MHC‐related protein‐1 (MR1). Using a combination of protein chemistry, mass spectrometry, cellular biology, structural biology and chemistry, we discovered MAIT cell ligands derived from folic acid (vitamin B9) and from an intermediate in the microbial biosynthesis of riboflavin (vitamin B2). Collectively, these studies revealed that in addition to peptide and lipid‐based Ags, small molecule natural product metabolites are also ligands that can activate T cells expressing αβ T‐cell receptors, and here we recount this discovery.